Análise comportamental e neuroquímica de ratos tratados com doses repetidas de lisdexanfetamina na infância e periadolescência - Okamura, Adriana Mary Nunes Costa (2019)
The notable increase in the number of attention deficit hyperactivity disorder (ADHD) cases in recent decades has attracted the attention of specialists for possible early and / or misdiagnosis of this disorder. Medications for the treatment of ADHD, for example, ritalin and, more recently, lisdexamphetamine (LDX-venvanse®) have as a mechanism of action potentiate of dopaminergic neurotransmission in brain areas such as the prefrontal cortex. Specifically LDX, approved by the FDA in 2007 for the treatment of children (from 6 years and adolescents and most recently approved for use in adults), is a prodrug of D-amphetamine. The increase in the consumption of these psycho-stimulants also occurred among youngsters and adults in order to increase cognitive capacity. Although the prescription of such drugs is aimed at the treatment of ADHD, narcolepsy and compulsive eating disorder, they have been widely used by healthy individuals. In view of this scenario the objective of the present work was to investigate behavioral and neurochemical changes induced by the repeated administration of LDX in rats at ages related to the childhood and adolescence of humans. For this, the animals were randomly separated into the following groups: group 1) animals treated for one week with LDX (10mg / kg); group 2) treated animals for two weeks LDX 10mg (in the first week) and 13 mg / kg (in the second week); group 3) rats treated for three weeks with LDX 10 (first week), 13 (second week) and 18 mg / kg (third week). Three other groups were treated with saline for the same time interval. Behavioral tests were performed to evaluate the exploratory and locomotor activity, anxiety and cognition levels, as well as neuro-oxidative and neuroinflammatory alterations. The results for behavioral tests showed that LDX administration did not bring about changes in operational memory (in the Y Maze test), however, it promoted short-term memory loss (in the NOR test) and an anxious-type behavior in the animals progressively throughout the treatment. Biochemical analyzes showed that the hippocampus and striatum regions of LDX treated mice for 3 weeks showed oxidative imbalance with decreased GSH levels and increased TBARS levels. It was also possible to observe a suggestive compensatory mechanism of IL-6, in addition to an increase in AT1 receptor expression in the hippocampus of the animals treated for three weeks with LDX. Finally, we can conclude from the findings of this study that the administration of the psychostimulant in question in healthy animals can cause cognitive and biochemical damage, especially if it is performed for long periods and at high doses.